MAKNA KEPEMIMPINAN DAN MANAJEMEN DALAM PENDIDIKAN - Ilham Sutrisna, Ilham Sutrisna; Lis Pahliani Aryati, Lis Pahliani Aryati; Saepul Bahri, Saepul Bahri; Eva Hastuti Serang, Eva Hastuti Serang; Ida Nurlela, Ida Nurlela; Muchtarom, Muchtarom (Wali Pikir: Journal Of Education, 2024)
Educational leadership and management are strategies that determine the emergence of institutional changes towards the better. Therefore, the quality of leadership and management must be improved from time to time in an effort to improve the quality of national education. In educational units, especially at the elementary school level, one of which is SD Negeri Malinggut, Sukabumi Regency. All principals are significant factors that enable the vision, mission and goals of education to be realized in this era of globalization.